Salinization of the Moszczenica river`s hyporheic zone in the vinciny of the Rogóźno salt dome - Ziułkiewicz, Maciej (Acta Geographica Lodziensia, 2022)
The Rogóźno salt dome has been recognised as the second largest diapir to have been discovered in Poland. It is located on the border of the Kuiavian Swell and the Łódź basin, where it is one of the elements outlining a north-eastern branch of the latter that is known as the Łódź basin. Among the many halokinetic forms, it is the only one in the region to have broken through the overlying Mesozoic deposits to come into direct contact with the overlying Cenozoic layer, resulting in specific hydrochemical effects. The genetically complex process that formed the regional river network in the Pleistocene and Holocene led to the formation of the Moszczenica channel above the dome. The river, together with its parent, the Bzura, acts as a regional drainage base for Cretaceous and Jurassic formations, meaning that the area around the dome (including the part around the diapir roof) is within its potential range. Between the river channel and the drained underground waters there is a zone in which the two environments interact. This is the Hyporheic Zone (HZ). Observations of hydraulic gradients between this zone and the water in the Moszczenica channel have shown that there may be deep water inflow within the streambed. This article presents the results of hydrochemical tests conducted in places where this phenomenon was most pronounced. The work aims to portray the hydrochemistry of the hyporheic waters and to connect it with the deep waters in the northern part of the Rogóźno salt dome. The following aquifers are distinguished in this area: - Holocene–Pleistocene multiaquifer formation, the lower part of which has a sub-artesian or artesian aquifer; - Neogene multiaquifer formation with a pressurised aquifer that in the lowest parts is associated with an upper lignite seam; - Palaeogene multiaquifer formation developed in mid-carbonaceous and subcarbonaceous sands; - Cretaceous multiaquifer formation (occurring only outside the deposit) of artesian character that is associated with the roof part of the complex of fissured carbonate rocks; - Jurassic multiaquifer formation (occurring only outside the deposit), which is formed by karst-fissure waters originating from a limestone complex; - Zechstein multiaquifer formation associated with the formations of the dome cap. Quaternary aquifers have markedly elevated values of TDS, chloride and sulphate concentrations and oxidability relative to the Quaternary floor and the Tertiary roof. Deeper, the values of these hydrochemical elements gradually increase, reaching the order of grams of salt per litre in the mid-carbonaceous horizon for TDS and 31 g·L-1 in the clay-gypsum cap. In the section in which it flows over the Rogóźno dome, the Moszczenica River does not show clear signs of geogenic salinity. The concentrations of sodium and chloride ions in the river are clearly higher before the dome than after. A gradientometer was used to measure hydraulic gradients and HZ samples within the Moszczenica streambed. The works focused on the river section below the bridge in Gieczno, where the IMGW–PIB water gauge is also installed. In selecting the research section, places with a positive hydraulic gradient and SEC higher than the river waters were sought. On this basis, part of the streambed was selected where the SEC values exceeded 500 μS·cm-1 (with an SEC of river waters in the 400–450 μS·cm-1 range). It is a straight section, free of obstacles impeding free water flow, featuring rapids and devoid of submerged macrophyte vegetation. Measurements of water temperature, pH, SEC and redox potential were taken in situ. The measurements showed that the inflow of water from the HZ clearly dominates over the entire test section. The average of five measurements in each cross-section is highest in the middle of the tested section, which also has the highest local negative gradient (˗0.04 cm·cm-1), i.e. a strong potential for river water infiltration into the streambed. The highest recorded SEC of hyporheic waters is more than double the highest value obtained for groundwater and more than seven times the SEC of the river waters. In terms of Total Hardness, five out of nine cases indicate that the hyporheic waters are hard, while the remaining cases are medium hardness, generally making them significantly harder than the ground-water and river waters. Na+ and Cl- in the hyporheic waters are distinguished by high concentrations in previously reported cases of mineral waters. The remaining cases of water from the HZ correspond to river or groundwater, while three “mineral water” intakes (GCZ, GO and WP; Fig. 7; Tab. 3) have significantly higher concentrations of Na+ and Cl- than other wells, though they also have less than half the level of mineral waters in the HZ. Br- concentrations confirm the peculiarity of the mineral waters against the background of other the hyporheic waters and the GO and GCZ (Tab. 3) wells among groundwaters. Br- concentrations in both groups are clearly related to each other (No. 1, 3 and 4, as well as GO and GCZ; Tab. 3). The studied part of the Moszczenica HZ is, hydrochemically, a very anisotropic environment. This is particularly evident when compared to the deep waters’ depth, nature of aquifer and contacts with the salt-bearing environment, and yet they represent only two hydrochemical types, while hyporheic waters represent five types. The analysis of the agglomerations of examined objects in terms of their standardised hydrochemical characteristics on a dendrogram (Fig. 6) showed that the hyporheic waters constitute a separate group of objects that are not related to the groundwaters. Only No. 8 and No. 9 (Fig. 6) are convergent with river waters, despite these locations seeing the draining of hyporheic waters, rather than infiltration by the waters of the Moszczenica. It is very interesting that the waters of the Moszczenica and its related part of the hyporheic zone (No. 8–9; Fig. 6) are more closely associated with the studied groundwater than with the waters of the rest of the HZ. Hence the conclusion that other groundwater flows into HZ than that from the tested wells. Therefore, it was necessary to refer to the archival data from which the data for the waters of the Palaeogene stage were obtained (from the zone of contact with the salt dome cap). The hypothesis about the presence of such waters in the hyporheic zone was confirmed using an HFE di-agram. The individual test points are generally located along the line of conservative mixing and are divided into two main groups. The saline environment is represented by the waters of GCZ, WP, GO and precisely from the Palaeogene stage overlying the dome, as well as from the HZ environment: No. 1, 3 and 4 (Fig. 7). The freshwater environment is represented by the waters of BR and KO and from HZ No. 5, 6, 7, 8 and 9 (Fig. 7) and the waters of the Moszczenica. Assuming, hypothetically, that the saline solution is flowing into the Moszczenica’s hyporheic zone from the bottom parts of the overlying Tertiary aquifer, their share in HZ was calculated. It turned out that this effect is greatest at points No. 1 and No. 4, much lower at No. 3, and negligible at No. 6 and 9 (Fig. 8). At the remaining points, the impact of saline waters is insignificant. The flow paths of the saline waters around the dome to the HZ are difficult to reconstruct due to the extent of disturbances in the rock formations in the zone above the dome. The effects of halokinesis, karstification of the dome cap and the exaration and accumulation activity of the ice sheet in the Pleistocene, as well as fluvial processes in the Holocene, all overlap here. The effects of human economic activities interfering with the course of the riverbed in this valley section since the early Middle Ages cannot be overlooked. In light of the results, it should be stated that the formation of the active HZ is favoured by the filtration properties of the Moszczenica’s bottom formations and the irregularity of the river slope resulting from the uplift of the substrate and its simultaneous local subsidence. Also of importance for the hydrodynamic and hydrostatic induction of flows in the hyporheic zone are the multitude of obstructions to the free flow of the Moszczenica’s waters in its lower section. They are natural and differ in spatial scale – from highly developed meanders, through rapids and fallen tree trunks in the channel, to various small morphological bedforms. Due to the rich economic past, there are also numerous dams for former water mills, along with a dense network (in some still passable) of mill chutes.The Moszczenica River’s HZ constitutes an effective barrier protecting the river against geogenic salinity. However, the progressive warming of the climate and the resulting changes in hydrological conditions may result in an increase in inflows of deep waters to the hyporheic zone, including of salty waters around salt dome.